The morphometric analysis of Al Nisr Valley Basin in Al Mithnab Governorate, in Kingdom of Saudi Arabia, using remote sensing and Geographic Information System - Al-Ruqi, Wedad Hammdan (Journal of natural sciences, life and applied sciences, 2023)
In this age, there is a noticeable increase in the interest in the applied studies based on remote sensing techniques and geographic information systems; such as extracting hydrological networks for river basins in arid and semi-arid regions, and calculating their morphometric characteristics, especially since most of their parts have been buried under the sands of dunes or reached by the planner and farmer through the landfilling and converting its tracks, which makes it an environmental hazard in case of floods. From this perspective, this study came into line with these research interests. To illustrate, it dealt with Al Nisr Valley Basin and its hydrological network was proven based on the (SRTM) model and the field study, and its morphometric characteristics were also analyzed. The results of the morphometric analysis of the form, area and topographic characteristics, as well as the analysis of the water network of Al Nisr Valley Basin, showed that its area had reached an amount of (86.23 km2), while the perimeter of the basin measured close to (102.60 km2), while the length and average width of the basin were respectively (31.33 km, 2.75 km), and that the valley did not complete its Erosion cycle according to the value of hipsometric integral, and that it has reached the fourth rank with a total of (71) watercourses. The results also showed that the basin tends to elongate away from the circular shape, which makes it of medium danger in the case of the surface runoffs of torrents, and this is supported by relief ratio, which reached (6 m/ km), meaning that in every one kilometer there is a relief of (6m), which is a low value that indicates the lack of the relief of the basin; as the longer the basin, the lower the relief ratio.
Keywords: remote sensing; hydrologic networks; morphometric; (SRTM); Al-Nisr Valley